The fall of Gondolin [large type] - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Wheeler Publishing Large Print hardcover, 2019)
Evil Morgoth rules over a vast military power from his fortress of Angband. Ulmo, the Lord of Waters, opposes him. Central to this enmity of the gods is the city of Gondolin, built and peopled by Noldorin Elves who rebelled against their rule and fled to Middle-earth. Into this world comes Tuor, cousin of Túrin. Guided unseen by Ulmo, Tuor sets out from the land of his birth on the fearful journey to Gondolin. The story -- only ninety-five pages long-- is accompanied by variant forms as well as essays and commentaries on Tolkien's work and on the source material. The final work of J.R.R. Tolkien's Middle-earth fiction, completing Christopher Tolkien's life-long achievement as the editor and curator of his father's manuscripts.